The Research on People’s Enterprise Skills in Serbia - Cvijanović, Janko; Rodica, Barbara; Vojnović, Boško; Živković, Milorad (Industrija, 2013)
In this paper authors analyse the attitudes and the perceptions of potential entrepreneurs from Mačva district in Serbia. The research based on GEM methodology shows that entrepreneurs have only modest enterprise skills. Such results were expected, due to the fact that entrepreneurship as a concept in this region is only in the early stages. Potential entrepreneurs in Mačva need additional training. The results also show that in average they graduated from secondary school and that they differ in age. It has been stated that potential entrepreneurs may play certain roles in their companies, but however, they are not ready to take the leading position yet.
Keywords: GEM||; ||; Perception||; Entrepreneurs||; Enterprise||